2021
DOI: 10.3390/ijerph182312527
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Air Pollution on Ischemic Heart Disease Hospitalizations: A Population-Based Time-Series Study in Wuhan, China, 2017–2018

Abstract: Evidence of the acute effects of air pollutants on ischemic heart disease (IHD) hospitalizations based on the entire population of a megacity in central China is lacking. All IHD hospitalization records from 2017 to 2018 were obtained from the Wuhan Information Center of Health and Family Planning. Daily air pollutant concentrations and meteorological data were synchronously collected from the Wuhan Environmental Protection Bureau. A time-series study using generalized additive models was conducted to systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Reduced particulate matter concentrations, however, are related to reductions in IHD mortality in as little as a few years. In this view, the improvement in quality of life and related health outcomes owing to lower concentrations of air pollutants might be seen by the population in a few years, essentially leading to the adoption of more rigorous policy choices on air quality in most parts of the world (9,13,45).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced particulate matter concentrations, however, are related to reductions in IHD mortality in as little as a few years. In this view, the improvement in quality of life and related health outcomes owing to lower concentrations of air pollutants might be seen by the population in a few years, essentially leading to the adoption of more rigorous policy choices on air quality in most parts of the world (9,13,45).…”
Section: Discussionmentioning
confidence: 99%
“…So et al [ 61 ] investigated the effects of air pollutants on the risk of ischaemic heart disease admissions in South Korea and reported that one-month exposure to SO 2 was related to 1.36-fold higher odds for ischaemic heart disease and one-year exposure to SO 2 and PM 10 was associated with 1.58 and 1.14-fold higher odds for ischaemic heart disease. One study conducted in China [ 62 ] also observed significant and positive correlations between admissions for ischaemic heart disease and short-term exposure to air pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason informing communities about bad air quality episodes should be regarded as a duty not a privilege rendered only to chosen ones. Multiple research links air pollution to respiratory diseases, including chronic obstructive pulmonary disease (COPD) 4 , asthma [5][6] ), lung cancer [7][8] , ischemia heart disease [9][10] , or even urinary bladder cancer 11 . Moreover, prolonged exposure to the air pollution can cause DNA damage 12 , oxidation stress and might even be associated with the brain damage, Alzheimer's disease (AD) and other neurodegenerative disorders [13][14] .…”
Section: Introductionmentioning
confidence: 99%